Genome-Wide Association Analysis of Age-Dependent Egg Weights in Chickens - Liu, Zhuang; Sun, Congjiao; Yan, Yiyuan; Li, Guangqi; Wu, Guiqin; Liu, Aiqiao; Yang, Ning (Frontiers in Genetics, 2018)
Egg weight (EW) is an economically-important trait and displays a consecutive increase with the hen’s age. Because extremely large eggs cause a range of problems in the poultry industry, we performed a genome-wide association study (GWAS) in order to identify genomic variations that are associated with EW. We utilized the Affymetrix 600K high density SNP array in a population of 1,078 hens at seven time points from day at first egg to 80 weeks age (EW80). Results reveal that a 90Kb genomic region (169.42Mb ~ 169.51Mb) in GGA1 is significantly associated with EW36 and is also potentially associated with egg weight at 28, 56 and 66 week of age. The leading SNP could account for 3.66% of the phenotypic variation, while two promising genes (DLEU7 and MIR15A) can be mapped to this narrow significant region and may affect EW in a pleiotropic manner. In addition, one gene (CECR2 on GGA1) and two genes (MEIS1 and SPRED2 on GGA3), which involved in the processes of embryogenesis and organogenesis, were also considered to be candidates related to first egg weight (FEW) and EW56, respectively. Findings in our study could provide worthy theoretical basis to generate eggs of ideal size based on marker assisted breeding selection.